Trajectory Optimization of Launch Vehicles Using Object-oriented Programming - Mota,Fábio Antônio da Silva (2018)
ABSTRACT: The aim of this study is to model launch vehicles with focus on 3-DOF trajectory optimization using a modular approach. Despite the large number of operational launch vehicles, they usually consist of basic components and subsystems. In other words, a launch vehicle is an assembly of stages, which in turn is divided into propellant system and engine, and the engine is an assembly of basic components such as pumps, turbines, combustion chamber, and nozzle. To allow future extension and reuse of the codes, a modular structure using object-oriented programming is used. Two formulations of state equations of the trajectory and two optimization methods are described. The launch vehicle performance will be measured by payload mass for a given mission. The simulations of the VLS-1, Ariane 5 and VLS-Alfa were performed and showed good agreement with the literature.